Phosphorylation of plant virus proteins: Analysis methods and biological functions - Zhuang, Xinjian; Guo, Xiao; Gu, Tianxiao; Xu, Xiaowei; Qin, Lang; Xu, Kai; He, Zhen; Zhang, Kun (Frontiers in Microbiology, 2022)
Phosphorylation is one of the most extensively investigated post-translational modifications orchestrating a variety of cellular signal transduction processes. Phosphorylation of virus-encoded proteins plays an important regulatory role in the life-cycle of their infection to plants. In recent years, the molecular mechanisms of the phosphorylation modification of plant viral proteins have been widely studied. Based on recent publications, we summarized the current phosphorylation modification analyses of plant viral proteins, and categorized their effects on biological functions according to the steps of the viral life-cycle. The present study provides a theoretical basis for the elucidating the molecular mechanism of viral infection. Further, it deepens our understanding of the biological functions of phosphorylation in interactions between plants and viruses.